Agile leadership for turbulent times : integrating your ego, eco and intuitive intelligence - Olivier, Sharon; Holscher, Frederick, 1948-; Williams, Colin, 1954- (Routledge, 2021)
"This thought provoking and engaging book is for you, whatever your seniority, in the private or public sector - if you are curious about the role and purpose of leadership in a turbulent world. It will help you become a more agile leader through understanding and integrating your ego, eco and intuitive intelligence. You will gain a deeper understanding of your unique leadership blend through a short diagnostic inventory, bringing insight about your strengths and what may be tripping you up. The book offers tips, ideas and practical suggestions on how to develop your ability to use the three intelligences in order to expand your leadership repertoire . It will help you enable the teams you lead to be more flexible, responsive and autonomous. The authors have drawn on their vast experience from the boardroom to the shop floor; the classroom and research around the world, to write an easy to-to-digest yet ground-breaking book that deals with the root causes of today's 21st Century leadership challenges. Its contents are straight forward and widely applicable"--